Advanced practice nursing : essentials for role development - Joel, Lucille A. (Philadelphia, PA : F.A. Davis Company, 2022)
'This text is written for the graduate-level student in advanced practice and is intended to address the nonclinical aspects of the role'--
Advanced practice nursing : doing what has to be done / Lynne M. Dunphy -- Emerging roles of the advanced practice nurse / Patricia A. Tabloski -- Role development : a theoretical perspective / Lucille A. Joel -- Educational preparation of advanced practice nurses : looking to the future / Phyllis Shanley Hansell -- Global perspectives on advanced nursing practice / Madrean Schober -- Advanced practice nurses and prescriptive authority / Jan Towers -- Credentialing and clinical privileges for the advanced practice nurse / Ann H. Cary and Mary C. Smolenski -- The kaleidoscope of collaborative practice / Alice F. Kuehn and Patricia Murphy -- Participation of the advanced practice nurse in health plans and quality initiatives / Rita Munley Gallagher -- Public policy and the advanced practice nurse / Marie-Eileen Onieal -- Resource management / Cindy Aiena, Eileen Flaherty, and Antigone Grasso -- Mediated roles : working with and through other people / Thomas D. Smith, Maria L. Vezina, Mary E. Samost, and Kelly Reilly -- Evidence-based practice / Christine A. Tanner, Deborah C. Messecar, and Basia Delawska-Elliott -- Advocacy and the advanced practice nurse / Andrea Brassard -- Case management and advanced practice nursing / Denise Fessler and Maryann Christopher -- The advanced practice nurse and research / Beth Quatrara and Dale Shaw -- Holism and complementary and integrative health approaches for the advanced practice nurse / Carole Ann Drick -- Basic skills for teaching and the advanced practice nurse / Christina Leonard, Valerie Sabol, and Marilyn H. Oermann -- Culture as a variable in practice / Mary Masterson Germain -- Conflict resolution in advanced practice nursing / David M. Price -- Leadership for APNs : if not now, when? / Edna Cadmus -- Information technology and the advanced practice nurse / Robert Scoloveno -- Writing for publication / Shirley A. Smoyak -- Measuring advanced practice nurse performance : outcome indicators, models of evaluation, and the issue of value / Shirley Girouard, Patricia DiFusco, and Joseph Jennas -- Advanced practice registered nurses : accomplishments, trends, and future development / Allyssa L. Harris, Jane M. Flanagan, and Dorothy A. Jones -- Starting a practice and practice management / Judith Barberio -- The advanced practice nurse as employee or independent contractor : legal and contractual considerations / Kathleen M. Gialanella -- The law, the courts, and the advanced practice nurse / David M. Keepnews -- It can happen to you : malpractice and the advanced practice nurse / Carolyn T. Torre -- Ethics and the advanced practice nurse / Carrie Scotto.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 04, 2023).
WorldCat record variable field(s) change: 050
Keywords: Nursing; Nursing -- Practice; Advanced Practice Nursing; Nurse's Role; Soins infirmiers -- Pratique; Nursing; Nursing -- Practice